Occupational Performance in the Discipline of Occupational Therapy During COVID‐19 at a Public University in KwaZulu‐Natal. - Ndaba, N.; Govender, P.; Naidoo, D.; Hilton, Claudia (Occupational Therapy International, 2025)
Introduction: The application of the person–environment–occupation–performance (PEOP) model in occupational therapy education offers valuable insights into the interaction between person, environment, and occupational factors and how these elements influenced the strategies used to adapt and navigate the transformation of health professions education during the COVID‐19 pandemic. This study explored how individual characteristics, contextual demands, and the nature of educational occupations shaped the adaptation and performance of educators and students. Materials and Methods: The study used a qualitative, exploratory research design at a public higher education institution (HEI) in South Africa, focusing on the occupational therapy program. Purposive sampling was used to recruit key participants (n = 44), including management, academic educators, clinical supervisors (academics), academic support educators, and occupational therapy students. Data collection occurred via the Zoom platform for 45–60‐min semistructured interviews. Thematic analysis, guided by the PEOP model, was employed to analyze qualitative data, which was recorded, transcribed, and coded using NVivo (Version 12 Pro). The study ensured trustworthiness and adherence to ethical principles. Results: The PEOP model was used as a framework to formulate the themes, namely, (1) person, (2) environment, (3) occupation, (4) occupational performance, and (5) occupational performance and participation. In the context of occupational therapy education, particular emphasis was placed on the adaptations and responses of educators and students as they navigated the demands of their educational occupations during the pandemic. Discussion: The curriculum underwent rapid adjustments, requiring theoretical instruction and clinical practice modifications. These changes posed significant challenges and highlighted pre‐existing gaps within HEIs, as experienced by educators and students. Conclusions: This study highlighted the importance of supporting optimal occupational performance among educators and students, emphasizing the necessity of providing adequate resources and support. This ensures the well‐being of educators and students, enabling effective engagement and participation as they navigate the evolving educational landscape.